Analytical Calculation of Critical Anchoring Length of Steel Bar and GFRP Antifloating Anchors in Rock Foundation. (12th January 2021) - Yan, Nan; Liu, Xueying; Zhang, Mingyi; Bai, Xiaoyu; Kuang, Zheng; Huang, Yongfeng; Jing, Desheng; Yan, Jun; Li, Cuicui; Wang, Zhongsheng
Abstract : Antifloating anchors are widely used during the construction of slab foundations to prevent uplift. However, existing methods for calculating the critical length of these anchors have limited capabilities and therefore require further research. As the mechanisms which govern the displacement and stability of antifloating anchors are closely related to those of piles subject to uplift, a simplified anchor model has been developed based on existing concentric thin-walled cylinder shear transfer models used for pile design. Analytical expressions for the critical length of the steel bar and GFRP (glass fiber reinforced polymer) antifloating anchors in rock are derived accordingly before demonstrating the validity of the method through engineering examples. The research results show that when the length of an antifloating anchor is less than a critical length, shear slip failure occurs between the anchor and surrounding material due to excessive shear stress. When the length of an anchor approaches the critical length, the shear stress gradually decreases to the undisturbed state. If the anchor length is larger than the critical length, the uplift loads are safely transferred to the ground without causing failure. The ratio of elastic modulus between the anchor and rock mass was found to be positively correlated with the critical anchoring length. Because the elastic modulus of GFRP bars is lower than that of steel bars, the critical anchoring length of GFRP bars is greater than that of steel bars under the same anchor-to-rock modulus ratio ( E a / E s ). The results show that the proposed calculation method for the critical length of antifloating anchors appears valid and could provide a theoretical basis for the design of antifloating anchors after further refinement.